Dampak Poligami Terhadap Pemenuhan Hak Istri Perspektif Keadilan Hakiki - Sinta Nopriana; Nyimas Lidya Putri Pertiwi; Firmansyah (Institut Agama Islam Negeri Metro, 2024)
The practice of polygamy has become a topic of interest in social, cultural and religious discussions in various parts of the world. In this context, the role of wives' rights and ultimate justice is an important focus. This aims to explore a deeper understanding of how polygamy affects wives' rights and how true justice can be realized in this context. Through a qualitative approach involving in-depth interviews with women and polygamists living in polygamous households and analysis of relevant legal texts, this research reveals a variety of experiences and perspectives related to polygamy. The research results show that the reality of polygamy can vary greatly, depending on factors such as cultural context, religion, and interpersonal dynamics within the family. Factors such as legal policies, social support, and religious understanding play a key role in determining the level of intrinsic justice felt by wives in polygamy.Regarding polygamy, wife's rights, and ultimate justice in this thesis not only provides deeper insight into the complex reality of this practice, but also raises important questions about how society and legal institutions can fight for the rights of women involved in polygamy. The practical implications of this research include the need for a more holistic and culturally sensitive approach in formulating policies and social interventions to support the welfare of wives in the context of polygamy in order to create the fairest possible justice for polygamous wives.